A New Economic Geography of Trade and Development? Governing South–South Trade, Value Chains and Production Networks. Issue 4 (1st October 2016) - Horner, Rory
Abstract: While South–South development cooperation has "win–-win" aims, it is unclear the extent to which its horizontal, mutually beneficial objectives translate into "South–South" trade and move beyond the asymmetrical nature of North–South trade. Global value chain and global production network research can make progress into an understanding of the dynamics of these emerging trade patterns. To date, however, such research has largely focused on the development prospects for firms and regions in the global South integrating into the production networks of lead firms from the global North. Evidence presented for the growth of South–South trade, including firms emerging from new home regions and the rise of new end markets in the global South, questions this focus. Emerging research suggests that the growth of South–South trade will be linked to a trade-off involving relatively easier access to Southern markets and potentially greater competition from competitors across the South. Avenues and questions for further research are identified here in terms of the governance, upgrading opportunities and territorial development outcomes associated with South–South chains and networks. Such research can move beyond win–win notions from development cooperation to highlight the commercial realities and very uneven geographies and development outcomes associated with expanding South–South trade.